Barium carbonate nanostructures: Biosynthesis and their biomedical applications. Issue 15 (1st August 2021) - Raessi, Mohamadali; Alijani, Hajar Q.; Nematollahi, Farima Foroughi; Baty, Roua S.; El-Saber Batiha, Gaber; Khan, Arif Ullah; Hashemi, Nooshin; Iravani, Siavash; Sharifi, Iraj; Aflatoonian, Mohammadreza; Khatami, Mehrdad
Abstract: In recent years, nanostructures and nanoarchitectures have attracted much attention in the development of biomedicine and nanomedicine. The plant-mediated synthesis of barium carbonate nanoparticles (BACN) has been performed using barium chloride and aqueous extract of natural sweetener (Stevia). In this study, the biosynthesis of BACN has been selected due to the useful medicinal potentials and suitable obtained biocompatibility of produced nanoparticles as well as its simplicity, lesser production steps, and cost-effectiveness. Barium carbonate nanostructures were characterized by X-ray diffraction, scanning electron microscopy, and transmission electron microscope. The toxicity of BACN on U87 brain cancer cells was evaluated based on MTT assay. According to the results, the prepared nanostructures can be employed for biomedical applications, especially cancer therapy. Graphical abstract: Image 1